Strategi Marketing melalui pelatihan Marketplace Shoppe untuk Meningkatkan Penjualan Home Industri Sambel Pecel di Desa Prajegan Sukorejo - Saputra, Rio Angga; Asfahani, Asfahani (Social Science Academic, 2024)
Digital marketing through marketplaces like Shopee is crucial for enhancing product sales. Marketplaces offer a broad platform that allows businesses to effectively reach customers, with features such as paid advertisements and data analytics supporting sales (Suryani & Hamidah, 2022; Rahmawati et al., 2023). This study focuses on digital marketing training for sambel pecel producers in Desa Prajegan Sukorejo, identifying that many entrepreneurs have not fully utilized Shopee's features. Surveys reveal that 65% of producers lack understanding in managing listings, and 72% struggle with promotional tools. The study aims to implement targeted Shopee training to improve sales and expand the market for sambel pecel products. The findings are expected to contribute to local economic development through better use of digital technology